Near- and Mid-ultraviolet Observations of X-6.3 Flare on 2024 February 22 Recorded by the Solar Ultraviolet Imaging Telescope on board Aditya-L1 - Soumya Roy; Durgesh Tripathi; Sreejith Padinhatteeri; A. N. Ramaprakash; Abhilash R. Sarwade; Nived V. N.; Janmejoy Sarkar; Rahul Gopalakrishnan; Rushikesh Deogaonkar; K. Sankarasubramanian; Sami K. Solanki; Dibyendu Nandy; et al. (The Astrophysical Journal Letters)
Solar flares are regularly observed in extreme-ultraviolet soft X-rays (SXRs) and hard X-rays (HXRs). However, those in near- and mid-ultraviolet are sparse. The Solar Ultraviolet Imaging Telescope (SUIT) on board the Aditya-L1, launched on 2023 September 2, provides regular observations in the 200–400 nm wavelength range through 11 filters. Here, we report the observation of the X6.3 flare on 2024 February 22 using eight narrowband (NB) filters of SUIT. We have also used co-spatiotemporal observations from Solar Dynamics Observatory/Atmospheric Imaging Assembly (SDO/AIA), Solar Orbiter/STIX, GONG H α , Aditya-L1/SoLEXS, and GOES. We obtained light curves over the flaring region from AIA 1600 and 1700 Å and GONG H α and compared them with the disk-integrated light curve obtained from GOES and SoLEXS SXRs and STIX HXRs. We find that the flare peaks in SUIT NB01, NB03, NB04, and NB08 filters simultaneously with HXRs 1600 and 1700 Å, along with the peak temperature obtained from SoLEXS. In contrast, in NB02 and NB05, the flare peaks ∼2 min later than the HXR peak, while in NB06 and NB07, the flare peaks ∼3 min after the GOES SXR peak. To the best of our knowledge, this is the first observation of a flare in these wavelengths (except in NB03, NB04, and NB05). Moreover, for the first time, we show the presence of a bright kernel in NB02. These results demonstrate the capabilities of SUIT observations in flare studies.